VOICES of YOUTH in WARTIME: Students at Kitchener-Waterloo Collegiate and Vocational School during the Second World War - Karn, Sara (Ontario History, 2018)
This article examines the experiences of adolescents in Canada during the Second World War through a case study of Kitchener-Waterloo Collegiate and Vocational School (K.C.I.) in Kitchener, Ontario. Although many prewar school activities remained a significant part of the student experience at K.C.I., the war impacted the students’ daily lives in ways specific to adolescents who attended school during this time period. Through their participation in various initiatives for the war effort, largely divided along gendered lines, students at K.C.I. contributed towards “school spirit” and developed a sense of responsibility as a future generation of Canadian citizens. This in-depth study of one Ontario high school in wartime demonstrates that age must be emphasized as a prominent factor in shaping experiences on the home front.